Populist Communication on Social Media (A Review of the Political Communication of the 2024 Presidential and Vice Presidential Candidates) - Putri Adhira (GoResearch - Research & Publishing House, 2024)
This research discusses the populist communication practices of presidential and vice presidential candidates in the 2024 elections on social media, focusing on the issues of community centrality, anti-elitism, and exclusionism. Populist communication, as a form of political persuasive communication, is known to be effective in attracting attention and mobilizing political support in various countries. Overall, the findings of this study show that the populist communication patterns carried out by the presidential and vice presidential candidates for the 2024 elections emphasize issues that are central to society. Interestingly, the issue of exclusionism, which involves the separation of groups, was not used by any of the presidential and vice-presidential pairs in their campaigns on social media. The emphasis on inclusivity is considered a strategy to maintain unity and support the spirit of diversity in Indonesia. However, some presidential and vice-presidential pairs utilized the issue of anti-elitism as a tool to increase their popularity and electability.